2022
DOI: 10.1038/s43587-022-00191-2
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic effects of mitochondria in aging

Abstract: itochondria are evolutionarily derived from alphaproteobacteria that evolved in symbiosis within eukaryotic cells 1 . Although most alphaproteobacterial genes were transferred to the eukaryotic nucleus, mitochondria retained their genome to translate the remaining protein-coding genes within their DNA. This requires complex coordination of the transcription and translation from two genomes, and the import and processing of proteins into the mitochondria in an ever-changing cellular milieu 2,3 . Disruption of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
75
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 111 publications
(99 citation statements)
references
References 255 publications
1
75
0
Order By: Relevance
“…Mitochondria are crucial to both physiology and pathophysiology, since their roles go beyond being the powerhouse of eukaryotic cells [ 63 ]. Literature has reported that mitochondrial function is declined with aging in humans [ 64 ], suggesting a connection between mitochondria with aging and age-related diseases [ 8 , 9 , 10 ]. A vicious cycle in which the increased ROS production induces mitochondrial dysfunction and vice versa is the basis of the free radical theory of aging proposed by Harman [ 11 ].…”
Section: Mitohormesis: a New Anti-aging Possibility Of H 2 ...mentioning
confidence: 99%
See 4 more Smart Citations
“…Mitochondria are crucial to both physiology and pathophysiology, since their roles go beyond being the powerhouse of eukaryotic cells [ 63 ]. Literature has reported that mitochondrial function is declined with aging in humans [ 64 ], suggesting a connection between mitochondria with aging and age-related diseases [ 8 , 9 , 10 ]. A vicious cycle in which the increased ROS production induces mitochondrial dysfunction and vice versa is the basis of the free radical theory of aging proposed by Harman [ 11 ].…”
Section: Mitohormesis: a New Anti-aging Possibility Of H 2 ...mentioning
confidence: 99%
“…The activation of the mitochondrial unfolded protein response acts as the first line of defense for relieving the stress. However, when the stress level is overwhelming, mitochondrial dynamics and mitochondrial autophagy (mitophagy) come into action for the removal of a part of the mitochondria or the entire damaged mitochondria, respectively [ 9 , 10 ]. It has been proposed that any defect in how the mitochondria sense and respond to a stress is critical for the initiation and progression of aging and age-related diseases [ 65 , 66 ], highlighting the potential implications of mitohormesis in maintaining mitochondrial function and promoting healthy aging.…”
Section: Mitohormesis: a New Anti-aging Possibility Of H 2 ...mentioning
confidence: 99%
See 3 more Smart Citations